The influence of heat-setting process on physical properties of ribbon-type fancy yarns and fabrics produced from them - Bedeloğlu, Ayşe (Inst Natl Cercetare-Dezvoltare Textile Pielarie-Bucuresti, 2014)
In this paper, the influence of heat-setting process on the properties of ribbon-type fancy yarns with different needle numbers and fabrics manufactured from them was investigated. With the increasing number of knitting needle, thicker fancy yams, higher strain, lower hairiness and so, thicker fabrics and higher mass per unit area and volume density, better abrasion resistance and higher thermal conductivity were obtained. The influence of heat-setting process was statistically significant on fancy yam and fabric properties at 95% confidence level (alpha = 0.05). Fabrics manufactured from heat-treatment applied yarns showed lower thermal absorptivity results giving warmer feeling compared to others.
Keywords: heat-setting; fancy yarn ribbon-type; fabric; physical properties